HUBUNGAN ANTARA KECERDASAN ( INTELEKTUAL, EMOSI, SPIRITUAL ) DENGAN PENERIMAAN DIRI PADA DEWASA MUDA PENYANDANG CACAT TUBUH DI BALAI BESAR REHABILITASI SOSIAL BINA DAKSA PROF. DR. SOEHARSO SURAKARTA - Anggraini, Desi; Wiyanti, Sri; Andayani, Tri Rejeki (Jurnal Ilmiah Psikologi Candrajiwa, 2012)
ABSTRACT CORRELATION BETWEEN INTELLIGENCE (INTELLECTUAL, EMOTIONAL, SPIRITUAL) TOWARDS SELF-ACCEPTANCE OF DIFABLE YOUNG ADULTHOOD IN BALAI BESAR REHABILITASI SOSIAL BINA DAKSA PROF.DR.SOEHARSO OF SURAKARTA Desi Anggraini Psychology Study Programme of Medical Faculty Sebelas Maret University Surakarta Â Self-acceptance is a positive attitude towards itself, in which individuals are able to accept the excess and the lack of their self, even if that is a difabilities condition. For young adulthood, of course, it was not an easy thing to accepted, either it was caused by native or by accident. The emotion flare which appeared from inside and outside of the self, such as perspective of others, might influence someone if they could accept or even reject theirself. In this case, the role of three kinds of intelligence(IQ,EQ,SQ) was very important to help young adulthood to overcome the pressure and be able to reach the realistic self-acceptance.The purposes of this research are to determine:1)Possitive correlation between intellectual intelligence, emotional intelligence, and spiritual intelligence with self-acceptance,2)Possitive correlation between intellectual intelligence with self-acceptance,3)Possitive correlation between emotional intelligence with self-acceptance, and 4) Possitive correlation between spiritual intelligence with self-acceptance. The population of this research were the students of Balai Besar Rehabilitasi Sosial Bina Daksa Prof.Dr.Soeharso Surakarta.They were 40 young aged adults between 20-30 years old, and minimal education junior high school.This research was population research.The data were collected using Self-Acceptance Scale, Emotional Intelligence Scale, Spiritual Intelligence Scale , and Culture Fair Intelligence Test Scale 3. This research used multivariate analysis techniques of non-parametric Ordinal Logistic Regression. The results of simultaneous test using the Likelihood Ratio Statistic (LR) indicates the value of X2=28,942 (X2hitung>X2tabel) and p = 0,000 (p<0,05), means that there was a positive correlation between intellectual intelligence, emotional intelligence, and spiritual intelligence with self-acceptance of difable young adulthood.Â Partial Test of Ordinal Logistic Regression is a Wald Test. The Wald result showed that there was a significant positive correlation between emotional intelligence with self-acceptance of difable young adulthood (p=0,007; p<0,05), there was a significant positive correlation between spiritual intelligence with self-acceptance of difable young adulthood ((p=0,042; p<0,05), and there was a very low correlation although has no significancy between intelectual intelligence with self-acceptance of difable young adulthood. Â Key Words: self-acceptance of difable, intelectual intelligence, emotional intelligence, spiritual intelligence